2021
DOI: 10.1002/ecm.1450
|View full text |Cite
|
Sign up to set email alerts
|

Water and nitrogen shape winter annual plant diversity and community composition in near‐urban Sonoran Desert preserves

Abstract: Increased nitrogen (N) deposition threatens global biodiversity, but its effects in arid urban ecosystems are not well studied. In addition to altered N availability, urban environments also experience increases in other pollutants, decreased population connectivity, and altered biotic interactions, which can further impact biodiversity. In deserts, annual plant communities make up most of the plant diversity, support wildlife, and contribute to nutrient cycling and ecosystem processes. Functional trade‐offs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 93 publications
0
6
1
Order By: Relevance
“…Furthermore, several studies showed that under N addition, moisture conditions indirectly affect the growth of plants by changing the composition and activity of microorganisms (Brisson et al, 2020;J. Li et al, 2020;Midolo et al, 2021;Wheeler et al, 2021); however, this phenomenon was not verified in this study. Therefore, future studies should focus on evaluating how changes in the soil microbial community affect the structure and composition of plant communities in arid and semiarid areas under both nitrogen and moisture conditions.…”
Section: Positive Effects Of N Addition On Plant Biomasscontrasting
confidence: 75%
“…Furthermore, several studies showed that under N addition, moisture conditions indirectly affect the growth of plants by changing the composition and activity of microorganisms (Brisson et al, 2020;J. Li et al, 2020;Midolo et al, 2021;Wheeler et al, 2021); however, this phenomenon was not verified in this study. Therefore, future studies should focus on evaluating how changes in the soil microbial community affect the structure and composition of plant communities in arid and semiarid areas under both nitrogen and moisture conditions.…”
Section: Positive Effects Of N Addition On Plant Biomasscontrasting
confidence: 75%
“…In both years, between mid-April and 20 August, fewer species developed compared to the corresponding springtime (from 20 March to mid-April) due to the "harsher" summer conditions for plant growth. Water availability affects plant diversity and has been found to increase in wetter years [53]; however, differences in precipitation were not significant. Therefore, without considering the effect of June-July precipitation, it is uncertain to establish what other parameters likely caused the population increase and longer presence within the meadow of Avena sterilis compared to 2016 where the population of Avena sterilis gradually decreased after mid-June 2016.…”
Section: Meadow Compositionmentioning
confidence: 89%
“…Trade‐offs among traits associated with plant growth and water use are known to play an important role in structuring annual plant communities in arid and semi‐arid ecosystems (Angert et al, 2007; Kimball, Gremer, et al, 2014; Schwinning & Ehleringer, 2001). N enrichment could reduce the competitive advantage of species with slower growth rates and more conservative water use, leading to the dominance of species with more rapid growth and loss of plant diversity (Wheeler et al, 2021). There is also evidence that some invasive annuals may escape such trade‐offs and exhibit ‘forbidden trait combinations’ that contribute to their competitive dominance over natives (Kimball, Gremer, et al, 2014), particularly in high N environments (Valliere, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, it appears that invasive annuals disproportionately benefit from early emergence and N addition compared with natives by rapidly accruing biomass and also increasing plant WUE (despite reduced allocation to roots). These functional differences and the ability of invasives to express traits associated with both rapid growth and drought tolerance may help to explain the ongoing loss of California's iconic wildflowers and richness declines in other threatened dryland ecosystems (Hernández et al, 2016; Minnich, 2008; Valliere et al, 2020; Wheeler et al, 2021).…”
Section: Discussionmentioning
confidence: 99%